Epidemiology of Intestinal Polyparasitism among Orang Asli School Children in Rural Malaysia - Al-Delaimy, A.K.; Al-Mekhlafi, H.M.; Nasr, N.A.; Sady, H.; Atroosh, W.M.; Nashiry, M.; Anuar, T.S.; Moktar, N.; Lim, Y.A.L.; Mahmud, R. (Public Library of Science, 2014)
Background